Variation in structural change around the world, 1985-2015: Patterns, causes, and implications - Adrian Wood (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
During 1985-2015, globalization intensified the factor-endowment-related pattern of sectoral specialization. In skill-abundant developed countries, manufacturing became more skill-intensive. In land-scarce developing East Asia, labour-intensive manufacturing expanded, especially in China. In land-abundant developing regions, however, manufacturing stagnated or declined, while in land-scarce South Asia manufacturing was held back by low literacy and weak infrastructure. The shares of service sectors in output and employment increased in most countries, but mainly for reasons unrelated to globalization. Changes in sectoral structure in the decades ahead are subject to much uncertainty, but will continue to be shaped by differences among countries in land abundance and skill supplies.
Keywords: F11; F14; F63; O14; O19; O57; 330; structural change; industrialization; globalization; Heckscher-Ohlin; factor endowments; world economy